2019
DOI: 10.1091/mbc.e19-05-0254
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatase inhibitor Sds23 regulates cell division symmetry in fission yeast

Abstract: Animal and fungal cells divide through the assembly, anchoring, and constriction of a contractile actomyosin ring (CAR) during cytokinesis. The timing and position of the CAR must be tightly controlled to prevent defects in cell division, but many of the underlying signaling events remain unknown. The conserved heterotrimeric protein phosphatase PP2A controls the timing of events in mitosis, and upstream pathways including Greatwall–Ensa regulate PP2A activity. A role for PP2A in CAR regulation has been less c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…In this study, we have identified a role for Sds23, a PP2A-family phosphatase inhibitor, in symmetric elongation of mitotic spindles in fission yeast. Past studies have shown a role for Sds23 in cell polarity and nutrient sensing (Deng, Lee, Schutt, & Moseley, 2017;Hanyu et al, 2009;Ishii, Kumada, Toda, & Yanagida, 1996), and we recently showed that Sds23 promotes positioning and anchoring of the cytokinetic ring in the cell middle (Schutt & Moseley, 2019). Here, we find that anaphase spindles elongate asymmetrically in sds23Δ cells, often fully entering one-half of the dividing cell.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In this study, we have identified a role for Sds23, a PP2A-family phosphatase inhibitor, in symmetric elongation of mitotic spindles in fission yeast. Past studies have shown a role for Sds23 in cell polarity and nutrient sensing (Deng, Lee, Schutt, & Moseley, 2017;Hanyu et al, 2009;Ishii, Kumada, Toda, & Yanagida, 1996), and we recently showed that Sds23 promotes positioning and anchoring of the cytokinetic ring in the cell middle (Schutt & Moseley, 2019). Here, we find that anaphase spindles elongate asymmetrically in sds23Δ cells, often fully entering one-half of the dividing cell.…”
Section: Introductionsupporting
confidence: 57%
“…Sds23 inhibits both Protein Phosphatase 6 (PP6) and Protein Phosphatase 2A (PP2A) (Deng et al, 2017;Hanyu et al, 2009;Schutt & Moseley, 2019). In fission yeast, both PP6 and PP2A-B55 (Pab1) are enriched in the nucleus, and PP2A-B56 (Par1) localizes to the SPBs during mitosis (Deng et al, 2017;Goshima, Iwasaki, Obuse, & Yanagida, 2003;Lahoz, Alcaide-Gavilán, Daga, & Jimenez, 2010;Le Goff et al, 2001).…”
Section: Discussionmentioning
confidence: 99%